Nederlands waterrecht voor niet-juristen - Mostert, Erik (TU Delft OPEN Books, 2019)
THIS IS THE FIRST EDITION, ONLY AVAILABLE ON REQUEST, PLEASE CONTACT Educationsupport THE 2ND EDITION IS AVILABLE HERE Dit boek biedt een algemene inleiding op het Nederlandse waterrecht voor niet-juristen. Het behandelt niet alleen het huidige waterrecht, maar ook hoe dit tot stand komt en wat het belang voor de praktijk van het waterbeheer is. Alle aspecten van het waterbeheer komen hierbij aan bod: de bestuurlijke organisatie van het waterbeheer, het waterkwaliteits- en -kwantiteitsbeheer, drinkwater en afvalwater, natuurbescherming, het Europese waterrecht, de ruimtelijke ordening, crisismanagement, financiering en rechtsbescherming. Alle gebruikte juridische begrippen worden duidelijk uitgelegd. Het boek is geschikt voor iedereen op academisch of HBO-niveau die geïnteresseerd is in het waterrecht en het waterbeheer. This book provides a general introduction to Dutch water law for non-lawyers. It covers not only current water law, but also how it came about and its relevance for the practice of water management. All aspects of water management are covered: the administrative organisation of water management, water quality and quantity management, drinking water and wastewater, nature protection, European water law, spatial planning, crisis management, financing, and legal protection. All legal terms used are clearly explained. The book suits anyone at an academic or college level interested in water law and water management.